Eksploitasi Anak Panti Asuhan dalam Novel Kado Terbaik karya J. S. Khairen - Zarwanda Adani Viandri; Yenni Hayati (Persona: Kajian Bahasa dan Sastra, 2023)
This study aims to describe the exploitation of orphanage children in the novel Kado Terbaik by J.S. Khairen, which belongs to a form of social violence. There are two forms of exploitation of orphanage children, namely the employment of minors and the trafficking of children. This type of research is literary research with descriptive methods. The research data are in the form of words, phrases, clauses, sentences, narration from the narrator, the speeches of the characters, and the actions of the characters related to the exploitation of children. The data collection method uses the listening method with advanced techniques in the form of note taking techniques. Data analysis techniques with content analysis, consisting of data reduction, data presentation, and data verification. The data validation technique uses the triangulation technique. Kado Terbaik by J.S. Khairen highlighted cases of child exploitation that occurred in orphanages in the form of employing underage children, such as begging, selling, busking, and some even committing criminal acts. In addition, there is also child trafficking in the form of cheating children and cases of child kidnapping. This is of course related to the sociological theory of literary works, reflecting what it is because the author connects directly with cases of child exploitation that have occurred in Indonesia. Thus, the author's way of expressing his concern about the case, the author makes the perpetrators of violence as one of the story characters whose function is to convey the author's message to his readers. So that readers can be more sensitive as well as empathetic to problems that occur in the real life of society.